The Role of Education through Animation Media on Knowledge and Attitudes Towards Balanced Nutrition in Elementary School Students - Juli Malinda; Iman Jalandri; Shelly Festilia Agusanty (Borneo Scientific Publishing, 2023)
Balanced nutrition is essential for a child's growth and development, enhancing their ability to learn and providing positive impacts for their future development. Knowledge and attitudes towards nutrition play a crucial role in determining the level of public health. Various nutritional and health problems can arise due to a lack of knowledge and attitudes regarding balanced nutrition. The aim of this study is to determine the effect of nutrition education through animation video media on knowledge and attitudes towards balanced nutrition among fifth-grade students at SDN 01 Teluk Batang, Kayong Utara. The research method used was a pre-experimental design with a